2020
DOI: 10.3389/fnint.2020.00004
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Audiovisual Processing in Children With a Sensory Processing Disorder (I): Behavioral and Electrophysiological Indices Under Speeded Response Conditions

Abstract: Background: Maladaptive reactivity to sensory inputs is commonly observed in neurodevelopmental disorders (e.g., autism, ADHD). Little is known, however, about the underlying neural mechanisms. For some children, atypical sensory reactivity is the primary complaint, despite absence of another identifiable neurodevelopmental diagnosis. Studying Sensory Processing Disorder (SPD) may well provide a window into the neuropathology of these symptoms. It has been proposed that a deficit in sensory integration underli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…For example, multisensory integration of auditory and somatosensory inputs (passively observed) was investigated in a cohort of 20 sensory over-responsive children using event-related potentials (ERPs;Brett-Green et al, 2010). The authors showed multisensory integration effects at multiple time points during sensory processing, so it was clear from the results that at least some aspects of integrative processing were intact (as in our partner article Molholm et al, 2020;this volume), but in that study, there was no comparison control group, so direct inferences about aberrant processing could not be made. Nonetheless, the authors did note some differences in the integration effects they observed relative to prior reports in the literature (Foxe et al, 2000).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, multisensory integration of auditory and somatosensory inputs (passively observed) was investigated in a cohort of 20 sensory over-responsive children using event-related potentials (ERPs;Brett-Green et al, 2010). The authors showed multisensory integration effects at multiple time points during sensory processing, so it was clear from the results that at least some aspects of integrative processing were intact (as in our partner article Molholm et al, 2020;this volume), but in that study, there was no comparison control group, so direct inferences about aberrant processing could not be made. Nonetheless, the authors did note some differences in the integration effects they observed relative to prior reports in the literature (Foxe et al, 2000).…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, we have shown multisensory processing deficits for much more fundamental stimuli than speech (i.e., simple tones and visual flashes) in ASD, which points to a more general multisensory processing deficit in that population. In a partner study to the current investigation of speech integration, we also assessed response speeds to very basic audiovisual inputs relative to unisensory inputs (Molholm et al, 2020 ). When neurotypical children and adults are asked to respond in this fashion, it is typical to observe a significantly speeded up response to bisensory audiovisual inputs relative to unisensory (i.e., auditory-alone or visual-alone inputs; Molholm et al, 2002 ; Mégevand et al, 2013 ), although this speeding is relatively modest in children in the age-range of the current study (Brandwein et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the cerebellum plays a role in multisensory processing, as its connectivity to the cerebral cortex is important for sensory integration across different modalities such as hearing, sight, touch and even smell (Cardon et al, 2017 ; Zhao et al, 2018 ; Sathyanesan et al, 2019 ). While investigation of the structural and functional aspects of sensory processing has begun in children with isolated SPD and those with sensory over-responsivity and autism (Bar-Shalita et al, 2009 ; Marco et al, 2011 ; Brandes-Aitken et al, 2018 ; Molholm et al, 2020 ), there has so far been no exploration of the role of the cerebellum in children with isolated SPD. We posit that the cerebellum may contribute to acquisition, discrimination, modulation, and integration of multisensory information for interpretation of the environment and generation of appropriate responses.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the cerebellum plays a role in multisensory processing, as its connectivity to the cerebral cortex is important for sensory integration across different modalities such as hearing, sight, touch and even smell (Cardon, Hepburn, and Rojas 2017; Sathyanesan et al 2019; Zhao et al 2018). While investigation of the structural and functional aspects of sensory processing has begun in children with isolated SPD and those with sensory over-responsivity and autism (Bar-Shalita et al 2009; Brandes-Aitken et al 2018; Marco et al 2011; Molholm et al 2020), there has so far been no exploration of the role of the cerebellum in children with isolated SPD. We posit that the cerebellum may contribute to acquisition, discrimination, modulation and integration of multisensory information for interpretation of the environment and generation of appropriate responses.…”
Section: Introductionmentioning
confidence: 99%